Molecular characterization of chikungunya virus during the 2019 outbreak in the Democratic Republic of the Congo. Issue 1 (1st January 2020) - Selhorst, Philippe; Makiala-Mandanda, Sheila; De Smet, Birgit; Mariën, Joachim; Anthony, Colin; Binene-Mbuka, Guillaume; De Weggheleire, Anja; Ilombe, Gillon; Kinganda-Lusamaki, Eddy; Pukuta-Simbu, Elisabeth; Lubula, Leopold; Mbala-Kingebeni, Placide; et al.
ABSTRACT: Early 2019, a chikungunya virus (CHIKV) outbreak hit the Democratic Republic of the Congo (DRC). Though seldomly deadly, this mosquito-borne disease presents as an acute febrile (poly)arthralgia often followed by long-term sequelae. Although Aedes aegypti is the primary vector, an amino acid substitution in the viral envelope gene E1 (A226V) is causing concern as it results in increased transmission by Aedes albopictus, a mosquito with a much wider geographical distribution. Between January and March 2019, we collected human and mosquito samples in Kinshasa and Kongo Central province (Kasangulu and Matadi). Of the patients that were tested within 7 days of symptom onset, 49.7% (87/175) were RT–qPCR positive, while in the mosquito samples CHIKV was found in 1/2 pools in Kinshasa, 5/6 pools in Kasangulu, and 8/26 pools in Matadi. Phylogenetic analysis on whole-genome sequences showed that the circulating strain formed a monophyletic group within the ECSA2 lineage and harboured the A226V mutation. Our sequences did not cluster with sequences from previously reported outbreaks in the DRC nor with other known A226V-containing ECSA2 strains. This indicates a scenario of convergent evolution where A226V was acquired independently in response to a similar selection pressure for transmission by Ae. albopictus . This is in line with our entomological data where we detected Ae. albopictu s more frequently than Ae. aegypti in two out of three affected areas. In conclusion, our findings suggest that CHIKV is adapting to the increased presence of Aedes albopictus in DRC.